Alkali and Alkaline Earth Metal Complexes as Versatile Catalysts for Ring‐Opening Polymerization of Cyclic Esters. Issue 8 (1st July 2021) - Bhattacharjee, Jayeeta; Sarkar, Alok; Panda, Tarun K.
Abstract: Biodegradable polyesters such as poly(ϵ‐caprolactone) (PCL) and poly(lactic acid) (PLA) have been considered for use in several areas, such as drug delivery devices, sutures, tissue engineering, and GBR membranes, due to its bio‐renewability, biodegradability, and biocompatibility. Several synthetic techniques for the preparation of polyesters have been reported in the literature, amongst which the ring‐opening polymerization (ROP) of cyclic esters is the most efficient. A convenient approach to access iso‐selective PLAs is polymerization of racemic lactide ( rac ‐LA), which shows excellent stereoregularity without the need for costly chiral auxiliaries or ligands. In this personal account, we review a series of methods that have been practiced to the synthesis of biodegradable polyesters from various cyclic monomers using alkali and alkaline earth metal complexes as efficient catalysts. Abstract : Recent study of synthesis and catalytic applications of earth abundant alkali and alkaline earth metal complexes with various ligand systems as efficient promoters of the ROP of cyclic esters such as ϵ‐caprolactone and rac ‐lactic acid.